Common fixed point theorems for sequences of fuzzy mappings - B. S. Lee; S. J. Cho (International Journal of Mathematics and Mathematical Sciences)
In this paper, we define g-contractive and g-contractive type fuzzy mappings and prove common fixed point theorems for sequences of fuzzy mappings on a complete metric linear space.